2020
DOI: 10.1136/bmjinnov-2020-000430
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, legal and administrative implications of the use of video and audio recording in an emergency department in Ontario, Canada

Abstract: While video and audio recording (VAR) of patients is well described for clinical research, its application to quality improvement in the emergency department has thus far been limited and hindered by potential obstacles. We believe this technology holds promise to incite marked systems improvement but only if deployed in a thoughtful and principled manner. Experts in clinical, regulatory, legal, quality improvement, patient safety and ethical domains collaborated to articulate the salient considerations and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Trauma video review is increasingly being used for quality improvement and education 49 . Introducing a video review program is not an insurmountable feat, as studies have clearly articulated the salient considerations and challenges of implementing trauma team video review programs at their respective institutions through a legal and ethical lens 50,51 . Video review technology incurs several advantages to comprehensively assess trauma team performance over in-person observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma video review is increasingly being used for quality improvement and education 49 . Introducing a video review program is not an insurmountable feat, as studies have clearly articulated the salient considerations and challenges of implementing trauma team video review programs at their respective institutions through a legal and ethical lens 50,51 . Video review technology incurs several advantages to comprehensively assess trauma team performance over in-person observation.…”
Section: Discussionmentioning
confidence: 99%
“…49 Introducing a video review program is not an insurmountable feat, as studies have clearly articulated the salient considerations and challenges of implementing trauma team video review programs at their respective institutions through a legal and ethical lens. 50,51 Video review technology incurs several advantages to comprehensively assess trauma team performance over in-person observation. Technology has improved to allow for continuously recorded high-definition audio and video feeds, which are then stored in encrypted files for security measures.…”
Section: Using Trauma Video Review To Assess Trauma Team Performancementioning
confidence: 99%
“…Due to cognitive limitations, bias, and clinical stressors, practitioner memory and recall can be sparse or flawed (6). Video and audio recording technology collects rich data outside of written notes and charts, even in chaotic and complex clinical situations.…”
Section: Therapeutic Documentation and Patient Reflectionmentioning
confidence: 99%
“…Yet, acceptance of VR can be hindered by feelings of embarrassment or anxiety for receiving negative feedback when someone is recorded 1 8–10. Previous studies showed that acceptance of video recording is based on educational usefulness and on the manner in which the VR conferences are conducted 8 11…”
Section: Introductionmentioning
confidence: 99%